Implementation of The Student Facilitator And Explaining Cooperative Learning Model to Improving Christian Religion Learning Outcomes - Adiline Waruwu (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
The Student Facilitator and Explaining Learning Model is a learning model in which students/learners learn to present ideas/opinions to other fellow students. The aims of this study were: (1) to describe the quality of the Christian Religion learning process at SMP Negeri 3 Idanogawo through the application of the Student Facilitator and Explaining cooperative learning model. (2) Describe the average learning outcomes of Christianity at SMP Negeri 3 Idanogawo by applying the Student Facilitator and Explaining cooperative learning model. This research was conducted at SMP Negeri 3 Idanogawo with the research subjects being Class VIII-B students in the odd semester of the 2019/2020 Academic Year, a total of 20 people. The research method used is classroom action research (CAR). The research instrument usedare: (1) observation sheets for students who are active in the learning process (2) observation sheets in the learning process of teacher respondents. (3) Quality questionnaires (4) Learning achievement tests, (5) Photo documentation. Based on data analysis, it was found that: (1) The learning process by applying the Student Facilitator and Explaining learning model in the learning process of Christianity at SMP Negeri 3 Idanogawo for the 2019/2020 academic year was good, the average quality questionnaire result at the end of cycle 1 was 63.19 % enough category and at the end of cycle 2 is 82.810% Good category. (2) Student learning outcomes in the subject of Christianity by applying the Student Facilitator and Explaining learning model in Class VIII-B of SMP Negeri 3 Idanogawo for the 2019/2020 academic year increased, it can be seen that in cycle I the average student learning outcomes reached 70 .15 in the